Cytolysins, Superantigens, and Penumonia due to Community-Associated Methicillin-Resistant Staphylococcus aureus - Schlievert, Patrick M. (2009)
This editorial evaluates data in an accompanying manuscript by Hongo et al. and includes comparison to other published data on virulence factors (cytolysins and superantigens) associated with or contributing to severe pulmonary diseases caused by methicillin-resistant Staphylococcus aureus (MRSA). The major conclusion of the Hongo et al. article is that studies to assess cytolysin functions in serious human MRSA infections must use non-murine models, since cytolysins, such as Panton-Valentine leukocidin (PVL), have limited activity in killing mouse polymorphonuclear leukocytes (PMNs), compared to killing human PMNs.